Asymptomatic Uncountable Urinary Bladder Stones Removal: Play the Winner - Hani H. Nour; Taha F. Mahmoud; Lemya Alzaabi (Dubai Medical Journal)
Urinary bladder stones are a common condition in elderly males, and they are usually related to infravesical obstruction secondary to prostate enlargement. Endoscopic management of bladder stone is the gold standard treatment; yet, in some cases, return to conventional open surgery is necessary. In our article, we reported the case of a 73-year-old male patient with accidentally discovered multiple urinary bladder stones. Cystolithotomy was the treatment of choice which went uneventfully with a smooth postoperative course.